PI3K pathway inhibitors: potential prospects as adjuncts to vaccine immunotherapy for glioblastoma. (June 2014) - Oh, Taemin; Ivan, Michael E; Sun, Matthew Z; Safaee, Michael; Fakurnejad, Shayan; Clark, Aaron J; Sayegh, Eli T; Bloch, Orin; Parsa, Andrew T
Constitutive activation of the PI3K pathway has been implicated in glioblastoma (GBM) pathogenesis. Pharmacologic inhibition can both inhibit tumor survival and downregulate expression of programmed death ligand-1, a protein highly expressed on glioma cells that strongly contributes to cancer immunosuppression. In that manner, PI3K pathway inhibitors can help optimize GBM vaccine immunotherapy. In this review, we describe and assess the potential integration of various classes of PI3K pathway inhibitors into GBM immunotherapy. While early-generation inhibitors have a wide range of immunosuppressive effects that could negate their antitumor potency, further work should better characterize how contemporary inhibitors affect the immune response. This will help determine if these inhibitors are truly a therapeutic avenue with a strong future in GBM immunotherapy.